2014
DOI: 10.1093/toxsci/kfu111
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Myocyte-Specific AHR Activation Phenocopies TCDD-Induced Toxicity in Zebrafish

Abstract: Exposure of zebrafish embryos to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) activates the zebrafish aryl hydrocarbon receptor 2 (AHR) to produce developmental and cardiovascular toxicity. AHR is found in the heart; however, AHR activation by TCDD is not confined to the heart and occurs throughout the organism. In order to understand the cause of cardiotoxicity, we constructed a constitutively active AHR (caAHR) based on the zebrafish AHR2 and expressed it specifically in cardiomyocytes. We show that AHR activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 59 publications
2
39
0
Order By: Relevance
“…If this occurs prior to kidney morphogenesis, it may result in a failure to form the pronephros. More broadly for zebrafish, secondary effects on jaw development due to edema (or loss of circulation) are a well-recognized adverse outcome pathway for cardiotoxicity caused by exposure to PAHs and dioxins (Incardona, et al, 2004;Lanham, et al, 2014).…”
Section: Osmoregulation and Circulation-dependent Adverse Outcome Patmentioning
confidence: 99%
See 1 more Smart Citation
“…If this occurs prior to kidney morphogenesis, it may result in a failure to form the pronephros. More broadly for zebrafish, secondary effects on jaw development due to edema (or loss of circulation) are a well-recognized adverse outcome pathway for cardiotoxicity caused by exposure to PAHs and dioxins (Incardona, et al, 2004;Lanham, et al, 2014).…”
Section: Osmoregulation and Circulation-dependent Adverse Outcome Patmentioning
confidence: 99%
“…While these compounds disrupt cardiac function through a variety of mechanisms (Clark et al, 2010;Incardona et al, 2005;Incardona et al, 2006;Incardona et al, 2011;Lanham et al, 2014;Prasch et al, 2003;Van Tiem and Di Giulio, 2011), they all cause embryonic heart failure at sufficiently high exposure concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…TCDD has a long half-life in tissues, and could thus cause prolonged AhR activation, which has been associated with toxic endpoints. 55 Nonetheless, it is remarkable that these AhR-responsive genes are significantly upregulated 10 months after a brief, low level TCDD exposure. In fact, the long-term histological and transcriptomic changes in these TCDD-treated zebrafish testes highlight the developmental basis for adult-onset disease.…”
Section: Figmentioning
confidence: 99%
“…Villeneuve et al (2014) used the adverse outcome pathway (AOP) framework to hypothesize possible mechanisms underlying impaired swim bladder inflation. Recent research has shown that compounds from a wide variety of chemical classes and modes of action impair swim bladder inflation (Hagenaars et al, 2014;Lanham et al, 2014;Wang et al, 2014), probably through a variety of underlying mechanisms (e.g., Bagci et al, 2015). However, the current description of AOPs related to swim bladder inflation do not provide information to understand the role of narcosis, and AOPs related to narcosis do not specifically focus on swim bladder inflation effects.…”
Section: Impaired Swim Bladder Inflation Was the Most Pronounced Morpmentioning
confidence: 99%